Characterization of Native Human Thrombopoietin in the Blood of Normal Individuals and of Patients with Haematologic Disorders - Matsumoto, Atsushi; Tahara, Tomoyuki; Morita, Haruhiko; Usuki, Kensuke; Ohashi, Hideya; Kokubo-Watarai, Atsuko; Takahashi, Kieko; Shimizu, Eiko; Tsunakawa, Hikaru; Ogami, Kinya; Miyazaki, Hiroshi; Urabe, Akio; Kato, Takashi (Thrombosis and Haemostasis, 1999)
Thrombopoietin (TPO) isolated from thrombocytopenic plasma of various animal species has previously been shown to comprise only truncated forms of the molecule, presumably generated by proteolysis. Native TPO has now been partially purified from normal human plasma by immunoaffinity chromatography and was confirmed to be biologically active. Gel filtration in the presence of SDS revealed that TPO eluted in two peaks: a major peak corresponding to the elution position of fully glycosylated recombinant human TPO (rhTPO) consisting of 332 amino acid residues, and a minor peak corresponding to a smaller molecular size. Immunoblot analysis also revealed that most plasma-derived TPO migrated at the same position as fully glycosylated rhTPO, corresponding to a molecular size of ~80 to 100 kDa. Furthermore, the size distribution of circulating TPO in patients with various haematologic disorders did not differ markedly from that of plasma-derived TPO from healthy individuals. These results indicate that the truncation of circulating TPO is not related to disease pa-thophysiology, and that the predominant form of TPO in blood is a biologically active ~80- to 100-kDa species. The size distribution of TPO extracted from normal platelets was similar to that of TPO in plasma; the proportion of truncated TPO was decreased by prior incubation of platelets with hirudin, indicating that the endogenous truncated TPO, at least in platelet extract, was generated by thrombin-mediated cleavage.